Understanding Early Childhood Resilience Following Neonatal Brain Injury From Parents' Perspectives Using a Mixed-Method Design. (April 2019) - Williams, Tricia S.; McDonald, Kyla P.; Roberts, Samantha D.; Westmacott, Robyn; Dlamini, Nomazulu; Tam, Emily W.Y.
Abstract: Objectives: The current study used a mixed-method design to qualitatively examine parents' definitions of resilience and factors they believed optimized their child's early outcome following neonatal brain injury. This was followed by quantitative analyses of early developmental and mental health outcomes and their relation to salient biopsychosocial factors. Methods: Participants were parents of children diagnosed with neonatal brain injury due to stroke or hypoxic-ischemic encephalopathy ( N =51; age range of children 18 months to 8 years). The Parent Experiences Questionnaire (PEQ) was used to qualitatively analyze parents' open-ended responses about their child's early experiences and outcome. The Child Behavior Checklist (CBCL) and Scales of Independent Behaviour Early Developmental Form (SIB-ED) parent ratings were used to measure child resilience from a quantitative perspective, identifying "at-risk" and "resilient" children using standard cutoffs. "Resilient" and "at-risk" children were compared on biopsychosocial variables using univariate t tests and chi-square analyses. Results: Parents provided five unique definitions of their child's positive outcomes, and many children demonstrated resilience based on parent perspectives and quantitative definitions. Supporting factors included close medical follow-up, early intervention, and intrinsic factors within the child and parent. Group comparisons of "resilient" and "at-risk" children highlighted the importance of parent mental health across these early developmental and mental health outcomes. Conclusions: Many children were described as resilient during the early years by parents using qualitative and quantitative approaches. Findings highlighted the importance of parent well-being in promoting optimal early outcomes. ( JINS, 2019, 25, 390–402.)